Physical representation of female character in children's novels by children - Muhsyanur, Muhsyanur; Suharti, Sri; Sudikan, Setya Yuwana (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
Literary work is a form and result of creative works of art whose objects are humans and their lives use language as a medium. Especially children's literature by children, basically has its own advantages. The storyline is unique and interesting and builds the expression of the child's world. This study aims to describe the physical aspects of female characters in children's novels by children. This paper is a qualitative research with a descriptive approach. The approach used in this study is a psychological literacy approach. The technique of collecting research data was done by reading carefully accompanied by marking. The analytical technique used is a symbolic hermeneutic technique. Based on the results of the study, the findings of this study relate to the physical aspects of female characters in children's novels which include physical aspects in terms of gender, physical aspects in terms of age, physical aspects in terms of facial characteristics, the physical aspect in terms of the clothes used, and the physical aspect in terms of the state of the body (senses). Key words: physical, representation, children's novel, and children's work